PROFESSORES DE INGLÊS: TRAJETÓRIA FORMATIVA E PROFISSIONAL - Fernandes, Karen de Azevedo (2008)
The present paper aims to discuss the formative and professional trajectory of English teachers that are teaching for the third degree, making deeper reflections about the difficulties or the facilities between the graduation and the beginning of the carrier as a teacher. Besides the carrying out of content s analyses got through the interviews, also the theoretical research was important to search a little bit about the history of the language teaching here in Brazil, as well as a study about the methods and approaches of English teaching so that we could analyse if the graduation of these professionals included or not the knowledge of these methods and if it was important not only for their formation but also for their acting in the class. Since my own experience as a private English teacher with difficulties during the teaching process, mainly due to my bad formation, I ve searched for some answers with these more experienced teachers that can contribute with the future English teachers to be more well formed and prepared to overcome the first difficulties of the carrier as well as to help them to reduce it , in some way so that they can teach with more confidence and competence, even because they are forming and preparing other teachers.(AU)